2019
DOI: 10.3791/58957
|View full text |Cite
|
Sign up to set email alerts
|

Using Microarrays to Interrogate Microenvironmental Impact on Cellular Phenotypes in Cancer

Abstract: Understanding the impact of the microenvironment on the phenotype of cells is a difficult problem due to the complex mixture of both soluble growth factors and matrix-associated proteins in the microenvironment in vivo. Furthermore, readily available reagents for the modeling of microenvironments in vitro typically utilize complex mixtures of proteins that are incompletely defined and suffer from batch to batch variability. The microenvironment microarray (MEMA) platform allows for the assessment of thousands … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
2
1

Relationship

5
4

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…MEMAs were produced as described previously (Smith et al, 2019;Watson et al, 2018) with several minor modifications. The same set of 45 ECM or ECM combinations that we previously reported were plated into the bottom of 96 well plates (Ibidi).…”
Section: Microenvironmental Microarray (Mema)mentioning
confidence: 99%
“…MEMAs were produced as described previously (Smith et al, 2019;Watson et al, 2018) with several minor modifications. The same set of 45 ECM or ECM combinations that we previously reported were plated into the bottom of 96 well plates (Ibidi).…”
Section: Microenvironmental Microarray (Mema)mentioning
confidence: 99%
“…To identify distinctive SASP factors potentially driving increased proliferation in recipient A549 cells, we used a microenvironment microarray (MEMA) platform. This recent technology allows the screening of the functional effects of multiple combinations of individual factors and cytokines in an unbiased high-throughput manner and the subsequent analysis of treated cell read-outs through advanced imaging 21, 22 . Remarkably, analysis of the proportion of high-EdU+ A549 cells upon 72 h treatment with an array of 64 human SASP-related ligands revealed that exposure to TGFβ-2 and TGFβ- 1 led to the highest A549 proliferation rate of all factors tested in the array (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We selected six ligands based on the results of two high-throughput microenvironment microarray (MEMA) screens of 3024 combinations of 63 soluble ligands and 48 insoluble ECM proteins 46 ; one screen with and another without EGF, a typical component of MCF10A growth medium 39 . We focused on collagen-1 as the insoluble ECM component and selected EGF, HGF, and OSM as ligands that increased growth in the absence of EGF; and BMP2, IFNG, TGFB as ligands that decreased growth in the presence of EGF (Sup.…”
Section: Approach To Generate a Lincs Me Perturbation Datasetmentioning
confidence: 99%